E- VOTTING PEMILIHAN WALIKOTA BENGKULU DI KOMISI PEMILIHAN UMUM (KPU) KOTA BENGKULU - Sulastri Sulastri; Leni Natalia Zulita (UNIVED Press, 2015)
E-voting is a process that utilizes electronic voting. Along with the times, has been a lot of research on the use of electronic voting process that replaces the voting process manually. During the mayoral election Bengkulu done manually, of course it requires a lot of time and errors in counting. To overcome this very necessary to saplikasi e-votting which can facilitate in Bengkulu City mayoral election and provide ease and speed of sound calculations. The system uses a data base system design and the design process. The design process that illustrates how the system processes the information that is shown by data flow diagrams (DAD). The e - voting produced to facilitate the election of the mayor of Bengkulu and countingKeywords: E - Votting , Mayor of the city of Bengkulu